2007
DOI: 10.1007/s10832-007-9181-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ag–ceramic composite electrodes to low firing piezoelectric multilayer ceramic actuators

Abstract: Ag-ceramic composite materials were investigated as low-cost internal electrodes for low firing piezoelectric multilayer ceramic actuators (MLCA). Ag-ceramic pastes were prepared by adding Pb(Mg 1/3 Nb 2/3 )O 3 -Pb (Zr 0.475 ,Ti 0.525 )O 3 (PMNZT) ceramic powders to a commercial Ag paste in the range of 0 to 50 wt.%. PMNZT/ Ag-PMNZT multilayered laminates were fabricated using tape casting and subsequently cofired at 925°C for 10 h. The addition of PMNZT into Ag electrode decreased the thermal shrinkage mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Currently most MLAs adopt expensive AgPd alloys as internal electrodes due to their thermal stability between piezoelectric ceramic layers throughout high temperature firing processes. Provided that low temperature co-firing of piezoceramic/metal multilayer laminates is established without significant degradation in piezoelectric properties, a cheaper conductor such as silver can be used as an inner electrode for MLAs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently most MLAs adopt expensive AgPd alloys as internal electrodes due to their thermal stability between piezoelectric ceramic layers throughout high temperature firing processes. Provided that low temperature co-firing of piezoceramic/metal multilayer laminates is established without significant degradation in piezoelectric properties, a cheaper conductor such as silver can be used as an inner electrode for MLAs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…5). In the range of apparent density between 5.80 and 5.87 g/cm 3 the values of apparent porosity are very similar. The values of relative density evaluated as the ratio of apparent density to the theoretical density are very similar (Table 1).…”
Section: Resultsmentioning
confidence: 68%
“…The values of relative density evaluated as the ratio of apparent density to the theoretical density are very similar (Table 1). Duran et al (2002) and Miot et al (1995) found that density of BaTiO3 sintered pellets based on the value of lattice constant is equal to 6.02 g/cm 3 . So, the obtained relative density is in agreement with the results of other authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal electrode behavior changes depending on sintering conditions. Thermal mismatch of electrode and ceramic causes deformation on inner electrode and delamination defect while sintering [30] and decrease in polarisation loop [31]. Also Ag-Pd electrode was not preferred before it was known that the presence of excess bismuth exists in the composition and would cause the reaction with palladium [32].…”
Section: Resultsmentioning
confidence: 99%